Adding Integers
If the numbers that you are adding have the same sign, then add the numbers and keep the sign.
Example:
-5 + (-6) = -11
Adding Numbers with Different Signs
If the numbers that you are adding have different (opposite) signs, then SUBTRACT the numbers and take the sign of the number with the largest absolute value.
Examples:
-6 + 5= -1
12 + (-4) = 8
Subtracting Integers
When subtracting integers, I use one main rule and that is to rewrite the subtracting problem as an addition problem. Then use the addition rules.
When you subtract, you are really adding the opposite, so I use theKeep-Change-Change rule.
The Keep-Change-Change rule means:
Keep the first number the same.
Change the minus sign to a plus sign.
Change the sign of the second number to its opposite.
Example:
12 - (-5) =
12 + 5 = 17
Multiplying and Dividing Integers
The great thing about multiplying and dividing integers is that there is two rules and they apply to both multiplication and division!
Again, you must analyze the signs of the numbers that you are multiplying or dividing.
The rules are:
If the signs are the same, then the answer is positive.
If the signs are different, then then answer is negative.
There are infinitely many solutions.
Algebraically, we can eliminate
and try to solve for
:
![x+y+z=1\implies z=1-x-y](https://tex.z-dn.net/?f=x%2By%2Bz%3D1%5Cimplies%20z%3D1-x-y)
Then
![x^2+y^2+(1-x-y)^2=1](https://tex.z-dn.net/?f=x%5E2%2By%5E2%2B%281-x-y%29%5E2%3D1)
![\implies x^2+y^2+1-2x+x^2-2y+y^2+2xy=1](https://tex.z-dn.net/?f=%5Cimplies%20x%5E2%2By%5E2%2B1-2x%2Bx%5E2-2y%2By%5E2%2B2xy%3D1)
![\implies x^2-x+y^2-y+xy=0](https://tex.z-dn.net/?f=%5Cimplies%20x%5E2-x%2By%5E2-y%2Bxy%3D0)
which is the equation of an ellipse.
Answer:
Answer is after 20 miles
Step-by-step explanation:
10 +2.5x = 3x
10 = 3x-2.5x
10=0.5x
10/.5=x
x=20
At 20 miles they both have a cost of 60
Answer: 2x+3
Step-by-step explanation:
9x+18=6y-3x Our goal is to isolate y.
Let's add 3x to both sides of the equation to cancel out that -3x on the right side.
12x+18=6y Because all of these integers are divisible by the gcf of 6, we can divide both sides of the equation by 6.
2x+3=y